PERALIHAN HAK ULAYAT MENURUT UNDANG-UNDANG NOMOR 18 TAHUN 2004 - Harniwati Harniwati (Ensiklopedia Social Review, 2019)
Customary land is a customary community's right that is recognized by positive law in Indonesia. In the Basic Agrarian Law expressly recognizes customary land as the existence of customary law. Law Number 18 of 2004 concerning plantations provides protection for customary land where if there is a transfer of customary rights to use rights for plantations for plantations, then protection must be given to customary communities that is, there must be agreement and consensus from the customary law community.